Aplikasi Slawe sebagai Piranti Pelayanan E- KTP dalam Sinkronisasi Notifikasi Layanan Pembuatan Kartu Tanda Penduduk: (Studi Pelayanan Publik Pembuatan E- KTP di Dinas Kependudukan dan Pencatatan Sipil, Kota Bengkulu dalam Masa Pandemi Covid-19) - Susianti, Yasmin Meri; Sugeng Suharto; Nour Farozi Agus (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
The aim of this research is to find out how the Slawe application as an E-KTP service tool synchronizes notifications and what causes notifications to be out of sync with E-KTP services in this application. The methods used are descriptive and qualitative, with purposive sampling techniques and data collection techniques through observation, interviews, and documentation. Based on research through aspects based on Law Number 95 of 2018 concerning Electronic-Based Service Systems (SPBE), responsiveness, assurance, and empathy, it is true that the Slawe application was not in sync with the E-KTP notification in July–December 2021. This is because the notifications on the application have not been updated. Meanwhile, in January–March 2022, the results showed that the Slawe application was in sync with its notifications and direct services at the Bengkulu City Dukcapil in terms of taking E-KTPs independently from January to March 2022. The suggestion from the researchers was that the Bengkulu City Population and Civil Registration Service needed to update notifications in the Slawe application according to the existing reality. The Bengkulu City Population and Civil Registration Service is carrying out repairs and maintenance on their Slawe website; this needs to be done on holidays or outside working hours. This is because many people feel disadvantaged if repairs or maintenance to the Slawe website are carried out on weekdays